The Effect of Social Problem Solving Skills on Coping Strategy and Optimism of High School Students in Bandar Lampung City, Indonesia - Utaminingsih, Diah (Jurnal Pendidikan Progresif, 2019)
The effect of social problem solving skills on coping strategy and optimism of high school students in Bandar Lampung City, Indonesia. Objectives: This study aims to examine the social effects of problem solving skills on optimism and coping strategies in 120 high school students in Bandar Lampung City. Methods: A comparative or ex-post causal causal study with data collection using conventional survey techniques. The research instrument was adapted from 5-Lickert scale of social problem solving inventory-revised (SPSI R). The data of this study were analyzed using ANOVA test and multiple linear regression. Findings: Multiple linear regression test for social problem solving skills–optimism and social problem solving skills-coping strategy have sig value 0.760 and 0.000, respectively. Conclusions: Social problem solving skills did not affect optimism, but directly affected students' coping strategies Keywords: social problem solving skill, optimism, coping strategy, secondary school students DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201901